Social Return on Investment: An alternative for the evaluation of zero waste management, during and after Covid-19 - Hochstrasser-Castillo, Nancy (Posgrados de la División de Ciencias Económica Administrativas, 2021)
Faced with the health emergency of the SARS COV2 respiratory syndrome, the generation of waste exposed to COVID-19 has increased, which do not have a treatment, so they require a management that involves removing them before their final disposal, becoming a source risk for the general population and for all those involved in its management. The objective is to present the social valuation of a public cleaning project in Metepec, which resulted in 1.27, with a return rate of 3%. This implies that the project has a positive social value effect, because it is greater than 1. It was decided to use the Social Return on Investment (SROI) tool to understand, measure and communicate the social, environmental and economic values that they can be created through the organization between the government and the interest groups, in order to carry out an adequate Management. Responding to the needs and circumstances of health problems that could affect the health of the population in future scenarios.